Development of Biopsy Gun for Aspiration and Drug Injection. (April 2015) - Kang, Hyun Guy; Cho, Sung Ho; Cho, Chang Nho; Kim, Kwang Gi
Tumor samples are required for pathological examinations, and different instruments are generally used to obtain samples of different types of tumors. Among the many methods available for obtaining tumor tissues, gun biopsy is widely used because it is much simpler than incisional biopsy and can collect many more samples than aspiration biopsy. However, conventional biopsy guns cannot simultaneously perform biopsy aspiration, bleeding prevention, and marker injection. In this study, we developed a biopsy gun that can simultaneously perform biopsy aspiration and sample collection, in addition to injecting a styptic agent and marker to prevent bleeding and contamination in the biopsy track. We then used a prototype to evaluate the feasibility of the developed device. The collectable sample size was also assessed. Performance of the biopsy aspiration feature was also evaluated, including the maximum aspiration viscosity. Finally, we tested the maximum amount of drug that can be injected. We found that the biopsy gun developed here is an alternative tool for biopsy collection with improved procedure safety and diagnostic accuracy.